(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2014)
Access to clean water and adequate sanitation has been a challenging issue in Kpakungu. Due to the unavailability of clean water sources and poor sanitation most of the inhabitants of Kpakungu are threaten with the spread of diseases such as diarrhoea and cholera and this has led to the degenerating situation of Kpakungu. Assessing the problems of water supply and sanitation in Kpakungu area of Minna, Niger State using GIS (Geographic Information System) is aimed at providing access to adequate portable water supply and a better sanitation through the use of research and advocacy. This is achieved by identifying the pattern of access to public water supply and sanitation in Kpakungu and the creation of a database of the existing water source and their yield was determined to enhance planning. This research involved the use of both primary and secondary data to achieve a thorough assessment of the problems of poor water supply and sanitation in the study area. It was discovered that the problems of poor water supply and sanitation often leave most women and children on queues for several hours and those that cannot endure are forced to travel long miles in search for alternative source of water, which may not be fit for drinking. In the light of this, mothers are prevented from domestic work and most children are kept away from school. At the end of the research water and sanitation blue print for the study area was designed and a proposal was sent to relevant government agencies and ministries for the provision of more sources of potable water in the community. In this regard, Public Private Dialogue (PPD) was initiated and adequate follow up process was made until the aim of the research was achieved.